Pathways to Promotion: Redesigning a Community College Faculty Promotion Process. Issue 1 (2nd January 2018) - Shattuck, Julie; Hawkins, Tony; Coldren, Gregory; Trigger, Kelly; Angleberger, Barbara; Dankanich, Nancy; Clayton, Aaron
ABSTRACT: This article reports on a design-based research project that is situated in a medium-size community college in Maryland. The project focused on exploring why the majority of full-time faculty was ranked as Assistant Professor or below, which did not reflect ranking at similar institutions. Under the leadership of the Provost, a task force analyzed the problem before designing a solution. The analysis phase of the project involved data collection and analysis through a faculty survey, a literature review, and a scan of other community colleges' promotion practices. The design phase used the findings from the analysis stage to redesign the promotion system and construct evaluation and promotion tools. The article gives insight into how the interests of diverse stakeholders can be taken into account when creating accessible, alternative pathways to promotion for faculty while also supporting the institution's mission and goals. For other community colleges looking at faculty promotion and evaluation, the results of this project highlight the importance of surveying faculty's experiences with the existing system; learning from best practices at other institutions; including the participation of the faculty and administrators in the redesign process; and allowing for ample time to thoroughly explore the situation from many angles before coming to consensus. Although limited to a particular context, this study may be of interest to both community college faculty and leadership.